Dietary consumption of selenium inversely associated with osteoporosis in postmenopausal women - Grili, Patricia Paula da Fonseca; Vidigal, Camila Vilarinho; Cruz, Geise Ferreira da; Albergaria, Ben Hur; Marques-Rocha, José Luiz; Pereira, Taísa Sabrina Silva; Guandalini, Valdete Regina (Frontiers in Nutrition, 2022)
Background: Osteoporosis is a skeletal disease characterized by reduced bone mineral density (BMD), which increases the risk of falls and fractures and reduces mobility. Some nutrients have a well-established role in maintaining bone health and preventing osteoporosis, while selenium (Se) has aroused interest in bone health possibly because of its anti-inflammatory and antioxidant capacity. The aim of this study was to evaluate the association between dietary Se consumption and BMD in postmenopausal women. Materials and methods: Cross-sectional, observational, analytical study carried out with women in menopause for at least 12 months, aged ≥ 50 years. Sociodemographic, lifestyle, and clinical data variables were studied. BMD was assessed using Dual Energy X-ray Absorptiometry (DXA) and the participants classified as having normal BMD, osteopenia, or osteoporosis. Dietary consumption of Se was assessed by the food frequency questionnaire (FFQ) and classified into quartiles of consumption. Multivariate logistic regression with three fit models was applied to investigate the association of BMD with Se consumption quartiles. The significance level adopted for all tests was 5.0%. Results: The final sample consisted of 124 women aged in average 66.8 ± 6.1 years and with a time since menopause of 19.6 ± 8.8 years. According to the BMD, 41.9% of the women had osteopenia and 36.3% osteoporosis. The mean consumption of Se was 154.4 ± 88.7 µg/day. The highest consumption of Se was observed among women with normal BMD (51.9%), whereas lower consumption levels were found in 57.7% of women with osteopenia and in 60.0% of women with osteoporosis (p = 0.003). In the multivariate analysis, after adjusting for possible confounding variables, Se remained associated with the group of women with osteoporosis. Postmenopausal women in the highest quartile (≥ 94.0 µg/day) of Se consumption had an OR of 0.02 (95%CI: 0.001-0.41; p = 0.012) of having osteoporosis when compared with women in the lowest quartile. Conclusion: Se consumption was associated with BMD and postmenopausal women with higher Se consumption were less likely to have osteoporosis.